(untitled) (University of Khartoum Engineering Journal, 2022)
The objective of this study is to investigate the usage of membrane reactor technology in the water-gas shift reaction. Furthermore an assessment of the optimum parameters for the maximum conversion of carbon monoxide was carried out. The water-gas shift reaction is a well-known step for upgrading carbon monoxide to carbon dioxide in the production of purified Hydrogen gas. More recently, a renewed interest in the water-gas reaction carried out in hydrogen selective membrane reactors has been observed, because of the growing use of polymeric electrolyte membrane fuel cells, that operate using high-purity hydrogen. Membrane reactors are viewed as an interesting technology in order to overcome the equilibrium conversion limitations in non-membrane reactors. Firstly, the modelling and simulation of the reactor without membrane was carried out, and the obtained results were validated against the experimental published results, then the membrane reactor was simulated by employing a Hydrogen-selective Palladium membrane. A one dimensional steady state model was developed; mass and heat balances were solved simultaneously using MATLAB software. It was found that the conversion of carbon monoxide reaches a maximum of 29% for the non-membrane reactor and 90% for the membrane reactor, which represents an improvement of 210%. It was found that the optimum operating condition for membrane reactor were temperatures of 740 K, pressure of 10 atm and a reactor length of 115 cm.